1987
DOI: 10.1200/jco.1987.5.10.1640
|View full text |Cite
|
Sign up to set email alerts
|

The effects of distance from primary treatment centers on survival among patients with multiple myeloma.

Abstract: Twenty-one comprehensive cancer centers participated in a national reporting system of common data items, recording information on all patients seen between 1977 and 1982. There were 240,531 patients who had data abstracted. This report describes 1,479 patients with multiple myeloma. Parameters that may effect the type of treatment given during the initial episode of therapy in the center and the effect of these characteristics on survival were studied. In the univariate analysis, age, treatment, and distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…Lenhard, et al (1987) reported on 1,479 newly diagnosed MM patients enrolled into the Centralized Cancer Patient Data System (CCPDS), a NCI supported multi-center collaborative database, between 1977 and 1982 19 . The investigators used the percentage of the population in each patient’s home zip code that were high school graduates during the 1970 census as a surrogate for SES.…”
Section: Discussionmentioning
confidence: 99%
“…Lenhard, et al (1987) reported on 1,479 newly diagnosed MM patients enrolled into the Centralized Cancer Patient Data System (CCPDS), a NCI supported multi-center collaborative database, between 1977 and 1982 19 . The investigators used the percentage of the population in each patient’s home zip code that were high school graduates during the 1970 census as a surrogate for SES.…”
Section: Discussionmentioning
confidence: 99%
“…We have no data in this setting: patient management seems quite similar in all the haematological institutions involved into the study. However, this a very complex matter; even the distance from the reference centre has been shown to be a significant factor in patient survival (Lenhart et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…These cases may represent statistical outliers, or they may be systematically different from the remainder of the population. Studies 15,24 have shown a protective benefit for patients who travel long distances; it is theorized that these cases represent the most empowered patients, who are not hindered by barriers such as travel distance.…”
Section: Distance To Diagnosing Providermentioning
confidence: 99%
“…Although increased travel distance is generally viewed as a barrier to screening, early diagnosis, and treatment, previous studies 15,17,[23][24][25] examining the role of travel distance for patients with cancer have had mixed results. We hypothesize that for patients with melanoma greater distance to a diagnosing provider is associated with increased Breslow thickness or stage at diagnosis.…”
mentioning
confidence: 99%